Non Hodgkins Lymphoma In Herniated Sigmoid Colon Presenting as Irreducible Left Sided Inguinal Hernia A Case Report And Review of Literature - Saha, Tapan Kumar; Hakim, HA Nazmul; Banik, Sanjit Kumar; Haque, Md Rajibul; Chowdhury, Tanvir Naz; Talukder, Md Tuhin (Journal of Dhaka Medical College, 2016)
Tumors presenting in the inguinal hernia sac are considered to be extremely rare, with the more common neoplasms metastazing from the gastro-intestinal tract, ovary and prostate. A case of non-Hodgkins lymphoma was identified in herniated sigmoid colonduring hernia repair while the hernia sac appeared unusual to the operating surgeon and the surgeon found sigmoid colon formed the posterior wall of hernia sac. This part of sigmoid colon could not be reduced and contained a firm growth, evaluation by the pathologists showed a malignant neoplasm, composed of anaplastic lymphocyte having excentical plasma nuclei and abundant cytoplasm. Histologic diagnosis is non-Hodgkins lymphoma. This is the first report of non-Hodgkins lymphoma found in herniated sigmoid colon. This case was reported in the Department of Surgery, Dhaka Medical College Hospital, Dhaka, and illustrates the value of routine microscopic evaluation of hernia sacs found from inguinal/femoral herniorraphies as it may be the primary presentation of an asymptomatic metastatic lymphoma. Additionally, it underscores the importance of surgeons role in screening by submitting only macroscopically abnormal specimans for microscopic evaluation. J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 73-75